Cardiac Strain Imaging Using Multi-Perspective Ultrafast Ultrasound - Liu, Peilu; Muller, Jan-Willem; Schwab, Hans-Martin; Lopata, Richard (Frontiers in Physics, 2022)
The heart is a complex organ with a high level of deformation occurring in different directions. Ultrasound imaging has proven to be a valuable tool to quantify these deformations. However, strain is not always measured accurately in vital parts of the heart when only using a single probe, even at a high frame rate, because of the anisotropic spatial resolution and contrast. Therefore, a multi-perspective ultrafast ultrasound (US) strain imaging method was developed, aiming at investigating improvements in strain while operating two probes at different relative angles. In an ex-vivo experiment of a beating porcine heart, parasternal short axis views of the left ventricle (LV) were acquired by two phased array probes with different relative angles (30° to 75°) at a frame rate of 170 frames per second (FPS). A fully automatic registration algorithm was developed to register the image datasets for all cases. Next, radio frequency (RF) based strain imaging was performed. Axial displacements were compounded based on the unit axial vectors of the dual probes to improve motion tracking and strain estimation. After performing multi-perspective strain imaging, compounded radial and circumferential strain both improve compared to single probe strain imaging. While increasing the inter-probe angle from 30° to 75°, the mean tracking error (ME), mean drift error (MDE) and strain variability (SV) decreased, and signal-to-noise ratio (SNRe) increased for both strain components. For the largest angle (75°), large reductions in ME (-42%), MDE (-50%) and SV (-48%) were observed. The SNRe increased by 253% and 39% for radial and circumferential strain, respectively, and strain curves revealed less noise for each region. In summary, a multi-perspective ultrafast US strain imaging method was introduced to improve cardiac strain estimation in an ex-vivo beating porcine heart setup.